2020
DOI: 10.17573/cepar.2020.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fiscal Policies on Western Balkan SMEs’ Growth: Evidence from Kosovo

Abstract: This paper analyses the impact of fiscal policies on increasing the capacity of SMEs from the manufacturing sector in the Western Balkans, with particular emphasis on those in Kosovo. To achieve empirical results, the data obtained from the opinions of the 100 analysed SMEs were pro­cessed through logistic regression. The SPSS statistical software was also used for these statistics. Based on literature review and empirical results, it has been concluded that fiscal policies have an impact on Kosovo SMEs growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Secondly, we recommend that the fiscal policy on SME should be ameliorated. Fiscal policies are very significant for the general development of all countries, (Jusufi and Gashi-Sadiku, 2020) and from their findings, they suggested that the exist a positive relationship between SME growth and fiscal packages which proves to the accurate. The productive tax rate in Cameroon stands at 57.7 percent according to the 2018 report on doing business in Cameroon.…”
Section: Policy Recommendation and Conclusionmentioning
confidence: 88%
“…Secondly, we recommend that the fiscal policy on SME should be ameliorated. Fiscal policies are very significant for the general development of all countries, (Jusufi and Gashi-Sadiku, 2020) and from their findings, they suggested that the exist a positive relationship between SME growth and fiscal packages which proves to the accurate. The productive tax rate in Cameroon stands at 57.7 percent according to the 2018 report on doing business in Cameroon.…”
Section: Policy Recommendation and Conclusionmentioning
confidence: 88%
“…Further, Wadesango et al (2020) [26] analysed the relationship between tax amnesty and tax compliance among SMEs in Zimbabwe and obtained an inverse relation. Several studies have turned their attention to assessing the effects of taxation on the performance and growth of SMEs [30][31][32][33] and mainly showed that these effects are negative. Thus, the study by Awotwe [31] analyses the effects of taxation on the financing decisions of SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jusufi and Sadiku [33] analysed the impact of fiscal policies on increases in the capacity of SMEs in the Western Balkans. The variables included in the study were: population number, nominal GDP at current prices, GDP per capita, unemployment rate, value-added services (% of GDP) and employment.…”
Section: Literature Reviewmentioning
confidence: 99%